Blue Laser Imaging with a Small-Caliber Endoscope Facilitates Detection of Early Gastric Cancer - Haruo Takahashi; Yoshimasa Miura; Hiroyuki Osawa; Takahito Takezawa; Yuji Ino; Masahiro Okada; Alan Kawarai Lefor; Hironori Yamamoto (Clinical Endoscopy, 2019)
Conventional endoscopy often misses early gastric cancers with minimal red discoloration because they cannot be distinguished from inflamed mucosa. We treated a patient with a small early gastric cancer that was difficult to diagnose using conventional endoscopy. Conventional endoscopy using a small-caliber endoscope showed only subtle red discoloration of the gastric mucosa. However, blue laser imaging showed a clearly discolored area measuring 10 mm in diameter around the red lesion, which was distinct from the surrounding inflamed mucosa. Irregular vessels on the tumor surface (suspicious for early gastric cancer) were observed even with small-caliber endoscopy. Biopsy revealed a well-moderately differentiated tubular adenocarcinoma, and endoscopic submucosal dissection was performed. Histopathological examination of the specimen confirmed well-moderately differentiated adenocarcinoma localized to the mucosa with slight depression compared to the surrounding mucosa, consistent with the endoscopic findings. This small early gastric cancer became clearly visible with blue laser imaging using small-caliber endoscopy.